(untitled) (Canadian Dermatology Today, 2022)
Immune checkpoint inhibitors (ICIs) are mainstay treatments for diverse malignancies. Approved ICIs in Canada include anti-PD-1 agents (nivolumab, pembrolizumab, cemiplimab, and dostarlimab), an anti-CTLA-4 agent (ipilimumab), and anti-PDL-1 agents (atezolizumab, avelumab, and durvalumab). ICIs are ground-breaking treatments, but have been associated with immune-related adverse events (irAEs) that can affect any organ system and which can be severe enough to necessitate treatment interruption or discontinuation. While the intended effect of ICIs is to activate the immune system against malignant cells, irAEs occur when this activation inadvertently targets host tissue. These occurrences appear idiosyncratic; predicting which patients will develop irAEs seems impossible.